Sosialisasi Budidaya Ikan Air Tawar di Sekolah Dasar Islam Terpadu Muslimat 1 Tarakan Kalimantan Utara - Diana Purnama Sari; Heni Irawati; Rini Mastuti; Awaludin Awaludin; Zainuddin Zainuddin (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
Freshwater fish farming has significant potential to support food security, environmental education, and community-based economic development. However, the limited practical knowledge of aquaculture among school educators often hinders the integration of fish farming activities into educational programs. Therefore, this community service activity was conducted to improve the competence of teachers and staff at SD IT Muslimat 1 Tarakan City in freshwater fish farming as a source of applied learning and a potential school-based entrepreneurial activity. The program involved 18 teachers and staff members who had limited prior experience in aquaculture practices. The quantitative target of the activity was to provide participants with fundamental knowledge and practical skills related to freshwater fish farming and to encourage the utilization of school facilities for educational fish culture activities. The activity was carried out on October 25, 2025, using interactive socialization and hands-on workshop methods. The training materials included the introduction of economically valuable freshwater fish species, such as tilapia and catfish, selection of culture media, water quality management, feeding practices, and pest and disease control. Participants actively engaged in both theoretical and practical sessions conducted at the school’s fish culture pond. The results indicated increased participant understanding of basic aquaculture techniques and the potential application of fish farming within the school environment. This activity is expected to support the eco-school program, strengthen environmental awareness, and promote sustainable educational and entrepreneurial initiatives.